Teaching Spanish in ElementarySchool: An Analysis from Sociodiscursive Interactionism - Blanca Araceli Rodríguez Hernández; Erika Michelle González López (Universidad Autónoma de Baja California, 2021)
This article presents the results of an analysis of the work of an elementary school teacher in a fifth-grade Spanish class. The theoretical frame of reference is sociodiscursive interactionism and its contributions to research on teachers' work based on prescribed, effective and represented work. To analyze the class, we revisit Riestra's (2008) proposal to study the instructions given and associated dialogues through self-confrontation between the researcher and the class teacher. The results show the importance of rephrasing instructions to understand how tasks progress and evaluate what is happening in the classroom. They also suggest that the reasons for rephrasing were linked both to the teacher (class management assumptions and confusion about the genre of the text) and to the prescribed work.